The influence of parents’ education anxiety on children’s learning anxiety: the mediating role of parenting style and the moderating effect of extracurricular tutoring - Yin, Xia; Zhang, HePing; Chen, Meng (Frontiers in Psychology, 2024)
Introduction: This study investigates the intricate relationship between parents' education anxiety and children's learning anxiety, examining the mediating role of parenting style and the moderating effect of extracurricular tutoring.Methods: Utilizing data from the "Survey of Parents and Students in Primary and Secondary Schools", the study employs stratified sampling (n=3298) and various psychological scales to measure education anxiety, parenting styles, and extracurricular tutoring.Results: This study reveals that parents' education anxiety significantly influences children's learning anxiety, with a notable positive correlation (r=0.301 ** ). Parenting styles particularly rejection and overprotection style increase this anxiety, while emotional warmth style decreases it.Academic tutoring serves as a moderator, reducing the impact of parental anxiety on children;s learning anxiety (β=-0.033, p<0.05).Discussion: The study underscores the importance of addressing internal family dynamics to alleviate education anxiety. It advocates for a balanced approach to tutoring, emphasizing the benefits of arts and sports activities in reducing learning anxiety. Parents should be encouraged to adopt emotionally warm parenting styles and to engage their children in a variety of extracurricular activities.